Psychometric properties of Liverpool Stoicism Scale (LSS) in a cohort of patients with resected cancer in adjuvant treatment - Calderon, Caterina; Ferrando, Pere Joan; Lorenzo-Seva, Urbano; Carmona-Bayonas, Alberto; Jara, Carlos; Ayala de la peña, Francisco; Beato, Carmen; Ramchandani, Avinash; Garcia, Teresa; Mangas-Izquierdo, Montserrat; et al. (Anales de Psicología / Annals of Psychology, 2017)
Stoicism has been used to describe a wide range of behaviors in the face of disease that go from silence, resistance to the adversity, or ‘to make the best of a bad disease’. This study pursued two objectives: 1) analyze the psychometric properties of the Spanish version of the LSS; 2) assess the relation between stoicism and gender, age, and the five-factor personality model. NEOcoping is a prospective, multicenter, observational, non-interventionist study. Patients were recruited consecutively at thirteen Spanish teaching hospitals. The following scales were administered: Liverpool Stoicism Scale (LSS) and Big Five Inventory (BFI-10). A total of 443 patients (250 females) with a mean age of 59.8 years (SD =12.3) were enrolled. Colon cancer was the most common (40.0%), followed by breast cancer (32.7%). At the total-scale level, mean LSS was lower than the originally reported British series and higher than Latvian sample. The four-factor structure fitted the data well, had a clear interpretation, and the derived scales showed acceptable reliabilities. The personality trait of introversion predicted 4.1% of the variance of stoicism (p<.001). The LSS scale demonstrates good psychometric properties to appraise stoicism in the Spanish population with resected cancer.